HUBUNGAN PEMBERIAN ASI EKSKLUSIF TERHADAP STATUS GIZIPADA BAYI USIA 7-8 BULAN DI WILAYAH PUSKESMAS TLOGOMULYO,KABUPATEN TEMANGGUNG TAHUN 2014 - Siwi Puspitasari; Wahyu Pujiastuti (JURNAL KEBIDANAN, 2015)
Exclusive breastfeeding has many benefits such as to improve intelligence, ASI has a psychological effect that can bring mothers with babies, and breast milk as the main nutrient in infants. Infants age is particularly vulnerable to nutritional problems of malnutrition, thus nutrients babies need for compliance in accordance with the needs of such infants exclusively breastfedTo determine the relationship between exclusive breastfeeding and nutritional status of infants aged 7-8 months at the health center with Tlogomulyo, Temanggung.Research is conduvted useanalytic correlation with cross sectional designon a sample of 47 cases, taken with a total sampling. Univariate analysis used is the dstribusi frequency, bivariate coefisien contingensi.The majority of infants aged 7-8 months in the region Tlogomulyo Health Center, Waterford given exclusive breastfeeding with 28 percent of respondents (59.6%) compared with exclusive breastfeeding is only 19 respondents (40.4%). Most respondents had a normal nutritional status were 21 respondents (44.7%). The results of the analysis of exclusive breastfeeding relationship with the nutritional status of infants aged 7-8 months resulted in p value of 0.014 and r value of 0.391, which means there is a connection because valuenya p-value 0.05 with a low level of closeness of the relationship..To mothers who had infants aged 0-6 months in order to remain granted exclusive breastfeeding until the baby is older than 6 months to meet the needs of the baby, and the head of the health center in order to improve the level of knowledge of mothers about exclusive breastfeeding and infant nutrition status